2021
DOI: 10.3390/su132212851
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Consumers’ Purchase Intention towards Electric Two-Wheelers

Abstract: The demand for electric vehicles (EVs) has significantly increased in recent years, but it represents only a tiny percentage of the total new vehicles sold globally. In 2021, the total sales of electric two-wheelers were less than 1% only. Therefore, the adoption of an electric two-wheeler (E2W) needs to be studied. This research develops a behavioral electric two-wheelers adoption intention model. The present study aimed to identify the factors that influence consumers’ intentions to adopt electric two-wheele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…As expected, perceived usefulness (Odds Ratio=1.965) was positively related to the higher inclination of riding an electric motorcycle [29][30][31]. The result validated the findings of prior studies on the intention to adopt electric motorcycles in Taiwan and India [5,7,9].…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…As expected, perceived usefulness (Odds Ratio=1.965) was positively related to the higher inclination of riding an electric motorcycle [29][30][31]. The result validated the findings of prior studies on the intention to adopt electric motorcycles in Taiwan and India [5,7,9].…”
Section: Resultssupporting
confidence: 84%
“…A recent study based on the responses of 182 Indian persons gathered from May to July of 2021 [9], the application of Structural Equation Modelling yields interesting results. Specifically, attitude towards electric motorcycles is positively influenced by environmental concern, perceived economic benefit, social influence, and charging infrastructure.…”
Section: Studies Related To Electric Motorcyclesmentioning
confidence: 99%
“…Customers are willing to adopt electric vehicles as environmental concerns continue to grow at an alarming rate (Ali & Naushad, 2022). Many researchers have studied the relationship between concern for the environment and consumer buying behavior and found that with higher environmental concern consumers are more likely to buy environmentally friendly products like electric two-wheelers (Jayasingh et. al, 2020).…”
Section: Environmental Concernmentioning
confidence: 99%
“…By using batteries as the main source, electric car designs can protect the environment from damage. Electric cars are an option (Abbasi, 2021;Jayasingh, 2021). At present the development of electric cars in terms of performance and efficiency continues to improve, and the increase in usage continues to increase (Dnishev and Alzhanova, 2016).…”
Section: Introductionmentioning
confidence: 99%